Application of SS-OCTA to evaluate the effects of long-term hydroxychloroquine treatment on retinal structure and microcirculation in patients with systemic lupus erythematosus - Xuemei Li; Chao Xiong; Shuilin Luo; Yunxiu Chen; Min Li; Siyi Wang; Yaohua Wang; Zhilin Wang; Rui Wu; Hongfei Liao (BMC Ophthalmology)
Key message Systemic lupus erythematosus, Hydroxychloroquine, retinal structure and microcirculation, SS-OCTA.